2019
DOI: 10.1111/mam.12175
|View full text |Cite
|
Sign up to set email alerts
|

Bat ecology and conservation in semi‐arid and arid landscapes: a global systematic review

Abstract: 1. Semi-arid and arid landscapes (dry-lands) cover 41% of the Earth's land surface over five continents. These areas are home to 55% of mammal species. Bats have the second highest species richness among mammals, and, although many species are adapted to arid conditions, they are particularly sensitive in these habitats and require conservation priority. 2. Information on bats in arid and semi-arid landscapes is scattered, patchy and focused on small-scale studies; therefore, we undertook a systematic review u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…4a; see Appendix S1 for the full breakdown of topics assigned). Similar results were reported by Lisón et al (2019) in semi-arid and arid landscapes, where the majority of studies were focused on habitat use and species inventories. Most of the studies were strongly biased towards insectivorous bats and were performed in temperate areas (Fig.…”
Section: Topics Of Studies and Species/assemblage Targetssupporting
confidence: 84%
See 2 more Smart Citations
“…4a; see Appendix S1 for the full breakdown of topics assigned). Similar results were reported by Lisón et al (2019) in semi-arid and arid landscapes, where the majority of studies were focused on habitat use and species inventories. Most of the studies were strongly biased towards insectivorous bats and were performed in temperate areas (Fig.…”
Section: Topics Of Studies and Species/assemblage Targetssupporting
confidence: 84%
“…2), probably due to financial limitations and ongoing social and political challenges (Racey 2013, Salvarina 2016. Lisón et al (2019) reported similar results, highlighting knowledge gaps in Africa, Asia, and Oceania with regard to bats in semi-arid and arid landscapes. For some countries (e.g.…”
Section: Geographical Distribution Of the Studiesmentioning
confidence: 65%
See 1 more Smart Citation
“…Bats are in most cases species of conservation concern due to their sensitivity to habitat changes, which make them vulnerable to a wide range of threats (Frick et al 2019;Russo et al 2017a, b). Our results suggest that maintaining low-intensity traditional farming in mountainous areas provide an asset to foster bat presence by offering profitable foraging conditions in otherwise relatively unproductive habitats (Lison et al 2020), where interspecific competition among bat species in the same foraging guild is more likely to occur (Salinas-Ramos et al 2020). Consequently, free-ranging and traditionally managed livestock should be seen as another management variable for bat conservation, in return for a potential ecosystem service provided by bats as pest suppressors.…”
Section: Discussionmentioning
confidence: 88%
“…Bats that call at low frequencies tend also to be fast, high-flying species, often of arid regions, that are not well surveyed using typical methods (Jones, 1999). For example, Lison et al (2019) advocated for more citizen science survey efforts to better populate distribution and abundance data sets of rare desert bats, and our study provides a way forward to help address this need. We recognize several ways to improve on our own study that will benefit others.…”
Section: Discussionmentioning
confidence: 99%